-6(7+X)=-42

Simple and best practice solution for -6(7+X)=-42 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6(7+X)=-42 equation:


Simplifying
-6(7 + X) = -42
(7 * -6 + X * -6) = -42
(-42 + -6X) = -42

Add '42' to each side of the equation.
-42 + 42 + -6X = -42 + 42

Combine like terms: -42 + 42 = 0
0 + -6X = -42 + 42
-6X = -42 + 42

Combine like terms: -42 + 42 = 0
-6X = 0

Solving
-6X = 0

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Divide each side by '-6'.
X = 0

Simplifying
X = 0

See similar equations:

| 7.3+z=60 | | 10a+15b=2x | | 2x+10=-3x | | 2x+5*3=11 | | 2ln(2*x+1)-3ln(x+1)+ln(x+1)=0 | | 3x+18=3x+34 | | 2(4-5x)=7-5(x-2) | | 20+1d=30+.5d | | 4n+3m=11 | | -30=5w+5 | | 64=9u-u | | 103+5x=63 | | 2(x)=54 | | x/-6=120 | | 2y+16=48 | | 2x-2-3=21-34x | | 31+4x=86 | | xln(x)-1=0 | | -54-8x=2x | | (1.09^x)/50 | | 4/5/5/4= | | v=1/3*b*h | | 7n-3n=3n+15 | | 3-12x+18=33 | | 9x-10y=24 | | -4-8=4(-3n+2) | | 9x-11=3x+8 | | 4x(3-y)=0 | | x+5(x-2)=8 | | 24+3x=3x(7-1) | | 9n+1=10 | | 10x=2+5 |

Equations solver categories